‘To Enjoin Virtue and Restrain Vice’: Modernizing Discourses and Engendered Traditions in Pakistan’s Jama’at‐e‐Islami - Jamal, Amina (Totalitarian movements and political religions, 2010)
A Quranic tradition related to moral disciplining of errant Muslims drives many projects of Islamic reform and has become central to the debates about gender and women’s human rights that have emerged in many Muslim‐majority and Islamic nation‐states. I argue that the reconceptualizing of amr bi’l ma’ruf wa nahi ‘anil munkar by the Jamaat‐e‐Islami marks a new space in Pakistani society for the fusing of modern citizenship and religious agency. I suggest that this space has enabled particular modes of public participation for women members of the Jama’at‐e‐Islami who have become strident critics of the feminist women’s movement in Pakistan. My engagement with ‘promoting good and forbidding evil’ is impelled by authoritative scholarly interventions that represent this tradition as an alternative ground for gendered religious agency to secular (feminist) concepts of the modern subject.